Postsynaptic scaffolds for nicotinic receptors on neurons - Neff, Robert A (Nature Publishing Group, 2009)
Complex postsynaptic scaffolds determine the structure and signaling capabilities of glutamatergic synapses. Recent studies indicate that some of the same scaffold components contribute to the formation and function of nicotinic synapses on neurons. PDZ-containing proteins comprising the PSD-95 family co-localize with nicotinic acetylcholine receptors (nAChRs) and mediate downstream signaling in the neurons. The PDZ-proteins also promote functional nicotinic innervation of the neurons, as does the scaffold protein APC and transmembrane proteins such as neuroligin and the EphB2 receptor. In addition, specific chaperones have been shown to facilitate nAChR assembly and transport to the cell surface. This review summarizes recent results in these areas and raises questions for the future about the mechanism and synaptic role of nAChR trafficking.